Music Education for Students with Visual and Hearing Impairments: A Scoping Review of Adaptive Technologies - Ayuningrum, Octavia Kusuma; Rita Milyartini; Widya Febiyanti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to map and synthesize how adaptive technologies are designed and implemented to support access, participation, and learning in music education for students with visual and hearing impairments. The study employed the Arksey and O’Malley scoping review framework, encompassing identification, screening, eligibility assessment, and data charting processes. Literature searches were conducted in Scopus, ERIC, and Google Scholar for articles published between 2016 and 2026. Fourteen studies met the inclusion criteria and were analyzed using thematic analysis. The findings identified five main categories of adaptive technologies: haptic and vibrotactile technologies, audio-based technologies, visual feedback technologies, Braille music technologies, and multimodal or multisensory technologies. These technologies were implemented through individual and collaborative music learning activities, structured training sessions, tactile and auditory instruction, and multisensory learning experiences. The reviewed studies demonstrated positive contributions to accessibility, musical participation, rhythm and pitch comprehension, musical performance, confidence, communication, and social participation among students with disabilities. However, most interventions remained exploratory, involving small samples and short implementation periods. Music educators should integrate adaptive technologies into curriculum-based instruction, technology developers should prioritize user-centered and sustainable designs, and policymakers should strengthen teacher training and accessibility support.